2019
DOI: 10.1128/mbio.02447-19
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Infects Osteoclasts and Replicates Intracellularly

Abstract: Osteomyelitis (OM), or inflammation of bone tissue, occurs most frequently as a result of bacterial infection and severely perturbs bone structure. OM is predominantly caused by Staphylococcus aureus, and even with proper treatment, OM has a high rate of recurrence and chronicity. While S. aureus has been shown to infect osteoblasts, it remains unclear whether osteoclasts (OCs) are also a target of intracellular infection. Here, we demonstrate the ability of S. aureus to intracellularly infect and divide withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 48 publications
2
53
0
1
Order By: Relevance
“…( A ) Low-power image of a multinucleated OC surrounded by mononuclear pre-OCs in the XY plane. In this image, the degree of co-localization of bacteria (green) and lysosomes (red), indicated in yellow, is particularly variable in the pre-OCs, but similar variation occurs in OCs as well, as previously shown [ 97 ]. ( B ) Images in the XZ plane along the dotted line in (A) show that the bacteria are inside, rather than on top of, the OC.…”
Section: Figuresupporting
confidence: 74%
See 2 more Smart Citations
“…( A ) Low-power image of a multinucleated OC surrounded by mononuclear pre-OCs in the XY plane. In this image, the degree of co-localization of bacteria (green) and lysosomes (red), indicated in yellow, is particularly variable in the pre-OCs, but similar variation occurs in OCs as well, as previously shown [ 97 ]. ( B ) Images in the XZ plane along the dotted line in (A) show that the bacteria are inside, rather than on top of, the OC.…”
Section: Figuresupporting
confidence: 74%
“…Recently, we showed that although OCs and their uncommitted myeloid progenitors take up S. aureus similarly, their handling of intracellular bacteria is quite different. OCs are not only unable to kill S. aureus , but also allow its intracellular proliferation, albeit with significant heterogeneity between cells [ 97 ] ( Figure 3 ). Mycobacterium tuberculosis , an obligate intracellular pathogen capable of infecting bone, has also been found to proliferate within OCs to a much higher level than in precursors [ 98 ].…”
Section: Intracellular Infection Of Ocs Providing a Proliferative mentioning
confidence: 99%
See 1 more Smart Citation
“…Dependence on purines has also been demonstrated for Francisella tularensis (4), Brucella abortus (5) and E. coli (6), among other bacteria. S. aureus has been shown to replicate in macrophages (22,24) and osteoclasts (25), but little is known about the nutritional requirements of S. aureus in the intracellular environment. Studies in S. aureus metabolism have identified that mutants in glycolysis (pfkA and pyk) (26) and lactate dehydrogenase (27) have reduced survival in RAW 264.7 macrophages, but no data is available on nucleotide biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being able to form biofilms, bacteria can also colonize human cells. In vitro and in vivo studies showed that S. aureus can persist intracellularly in a lot of cells found in the bone environment, including bone cells such as osteoblasts, osteoclasts, and osteocytes, and also in immune cells such as Kupffer cells and macrophages in the case of systemic infection [ 35 , 36 , 37 , 38 , 39 ]. However, continued research is warranted to highlight the impact of internalization in each cell type on the durability and the severity of the infection.…”
Section: Role Of Bacterial Biofilm In Prosthetic Joint Infectionsmentioning
confidence: 99%